WHERE IS THE GLOBAL SOUTH? A SYSTEMATIC REVIEW OF GEOPOLITICAL REPRESENTATION IN DIGITAL ACTIVISM RESEARCH - Oezkula, Suay Melisa; Reilly, Paul (AoIR Selected Papers of Internet Research, 2023)
The diffused and global nature of many digital contexts makes it difficult to trace what regions (incl. The Global South) are represented in digital activism research. This systematic review aimed at providing a sense of this distribution in digital activism research between 2011-2018 (N= 315 articles) through a coding of categories tied to region and marginality. These factors included choice of case study, case study origin and location, author origin, region and ethnic foci of the publishing journals, and digital/ social media platform (as tied to specific user demographics). The results show a high representation of Global North cases and campaigns, as well as non-region-specific and high-visibility social media groupings (e.g. hashtag publics), particularly the case in platform-based research (i.e. digital data sources). This means that researchers may need to rethink (a) where (e.g. which platform spaces) and how disadvantaged and less visible social groups are represented online, (b) which precise ethnic or regional groups such research is meant to capture in digital spaces, as well as (c) what these hindrances mean for democratic participation, grassroots movements, and counterpublics.